The Traditional Uses, Phytochemistry, Pharmacology, Toxicology, and Clinical Uses of Metagentiana Rhodantha (Franch.) T.N.Ho and S.W.Liu, an Ethnomedicine in Southwest China - Chang, Botao; Tang, Songjiang; Chen, Rong; Xiao, Nan; Zhu, Jingsong; Tian, Mengxian; Jiang, Huizhong; Li, Xi; Jian, Zhonglu; Han, Xu; Gao, Ying; Yao, Qi (Frontiers in Pharmacology, 2021)
Background: Metagentiana rhodantha (Franch.) T.N.Ho & S.W.Liu (MRF) belongs to Gentianales, and it is often called Hong-hua-long-dan in Chinese. Traditionally, it has been used to cure acute icteric hepatitis, sore throat, dysentery, acute gastritis, carbuncle, and furuncle based on traditional Chinese medicine (TCM) concepts. Aim of study: This review manages to provide a critical and comprehensive analysis on the traditional uses, phytochemistry, pharmacology, toxicology, and applications of MRF and to evaluate the therapeutic potential of this plant. Methods: Relevant data mainly literatures on MRF were selected from available database. Results: The heat-clearing and removing the phlegm, and purging fire and removing toxicity of MRF contribute to its dispelling jaundice, and clearing lung heat and cough. The phytochemistry reveals that the compounds isolated from this plant include iridoids and secoiridoids, phenolic acids, ketones, triterpenoids, flavonoids, benzophenone glycosides, and others. And mangiferin is a characteristic substance from this plant. The pharmacological research show that some extracts and compounds derived from MRF exhibit anti-inflammatory, anti-nocieptive, antipyretic, anti-tumor, antibacterial, hepatoprotective, cardioprotective, hypoglycemic, and immnomodulatory effects which are closely related to the traditional uses of this plant. The toxicological studies suggest that the characteristic compound MAF is less toxic in mouse and dog. Nowadays, Chinese patent drugs such as Feilike Jiaonang and Kangfuling Jiaonang containing MRF have been prepared to cure cough, asthma, chronic bronchitis, dysmenorrhea, and appendagitis. Conclusions: Although the cited studies provide some references for future research and development of MRF, it is still necessary to systemically evaluate chemistry, pharmacology, and safety of the extracts or the compounds from this plant before the future clinical trials. In addition, except lung infection-related diseases and gynecological diseases, analgesia, anti-tumor and hpyerglycemia may be new and prior therapeutic scopes of this ethnomedicine which is widely used by minor nations in the southwest of China in the future.